AAAP meeting: Providers urged to voice concerns over marijuana. Issue 48 (16th December 2022) - Enos, Gary
Abstract : Having an honest, fact‐based conversation with patients or policymakers about the dangers of cannabis means having to navigate an array of contradictions, panelists at a first‐day symposium of the American Academy of Addiction Psychiatry (AAAP) annual meeting acknowledged. Participants in the Dec. 8 session in Naples, Florida cited these among the most prominent contradictions that complicate today's discussions around cannabis.